Medeteksi Indikasi Kecurangan Laporan Keuangan di BUMN: Analisis Tata Kelola Perusahaan dan Moderasi Biaya Audit - Annisa Diah Kusuma Piri; Siti Mutmainah (Jurnal Proaksi, 2025)
Main Purpose - This study examines the role of audit fees as a moderating variable in the relationship between corporate governance and financial statement fraud indications in state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Method - The population includes all State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period and a sample of 100 companies was selected using the purposive sampling technique. Main Findings - The results show that board meeting frequency has a negative effect on financial statement fraud indications, while independent commissioners have a positive effect. Additionally, audit fees strengthen the influence of board meeting frequency on financial statement fraud indications but weaken the effect of independent commissioners. Theory and Practical Implications - These findings encourage companies to strengthen corporate governance systems and serve as a basis for setting optimal audit fee policies to enhance audit quality and supervisory effectiveness in preventing financial statement fraud indications. Novelty - This study highlights the role of audit fees in enhancing corporate governance effectiveness in preventing financial statement fraud indications, an aspect that has received limited attention in previous research.